Pengaruh Serat Baja Terhadap Kuat Tarik Lentur Balok Beton yang Disambung - Utami, Tri Ratna; Noorhidana, Vera Agustriana; Sebayang, Surya; Helmi, Masdar (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2022)
The casting of concrete at different times often occurs, this is due to insufficient casting time, expansion or connection of structural components, strengthening of structures with additional dimensions, and so on. Thus there will be the addition of a new layer of concrete (overlay). This study is to determine the flexural tensile strength of concrete beams for joining old concrete and new concrete with the addition of steel fiber volume fractions of 0%, 1%, 1.5%, and 2% in the substrate layers overlay and also the compressive strength of the concrete in each layer. The samples in this study were beams (15 x 15 x 60 cm) with a thickness of 7.5 cm for substrate and overlay for flexural tensile strength testing and cylinders (15 cm in diameter and 30 cm in height) for compressive strength testing. From the results of the study, it was found that the flexural tensile strength of the beam with the addition of steel fibers in the substrate layer was higher than the addition of steel fibers in the overlay layer. The addition of steel fibers in the substrate and overlay layers makes the beam more ductile. The maximum flexural tensile strength of the beam with the addition of steel fibers in the substrate layer occurs at  volume fraction 1.5%, has an increase of 114.03% from the joint beam without steel fibers while the addition of steel fibers in the overlay layer occurs at volume fraction 2%, has an increase of 8.66% of the joint beams without steel fibers.